2022
DOI: 10.1042/bsr20220426
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and serotonin deficiency in major depressive disorder: molecular docking of antidepressant and anti-inflammatory drugs to tryptophan and indoleamine 2,3-dioxygenases

Abstract: The roles of the kynurenine pathway (KP) of tryptophan (Trp) degradation in serotonin deficiency in major depressive disorder (MDD) and the associated inflammatory state are considered in the present study. Using molecular docking in silico, we demonstrate binding of antidepressants to the crystal structure of tryptophan 2,3-dioxygenase (TDO), but not to indoleamine 2,3-dioxygenase (IDO). TDO is inhibited by a wide range of antidepressant drugs. The rapidly acting antidepressant ketamine does not dock to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The promotion of the kynurenine pathway has been reported to result in the inhibition of serotonin synthesis [ 51 ], thus strongly supporting the notion that venlafaxine may decrease plasma serotonin concentrations by activating the kynurenine pathway. Some metabolites in the kynurenine pathway, including kynurenic acid, have been described as being neuroprotective in the depression setting [ 52 , 53 , 54 , 55 , 56 ]. Interestingly, kynurenic acid was the only negatively correlated metabolite with venlafaxine.…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of the kynurenine pathway has been reported to result in the inhibition of serotonin synthesis [ 51 ], thus strongly supporting the notion that venlafaxine may decrease plasma serotonin concentrations by activating the kynurenine pathway. Some metabolites in the kynurenine pathway, including kynurenic acid, have been described as being neuroprotective in the depression setting [ 52 , 53 , 54 , 55 , 56 ]. Interestingly, kynurenic acid was the only negatively correlated metabolite with venlafaxine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inflammatory cytokines released in the process of COVID-19 inflammation activate both the HPA–axis and the IDO enzyme, increasing the levels of toxic metabolites of the Kyn pathway, which increases overall neuroinflammation and neuronal death, promoting depressive conditions [ 52 ]. Additionally, antidepressants with anti-inflammatory properties inhibit IDO induction by decreasing the levels of proinflammatory cytokines in immune-activated individuals, contributing to attenuation of depressive symptoms [ 53 ]. The role of the immune system in depression is also supported by the homeostasis of glutamatergic neurotransmission, which can be regulated by the QA/Kyna ratio, synthetized by microglia and astrocytes, respectively [ 54 ].…”
Section: Trp Metabolism In Depression—an Overlookmentioning
confidence: 99%
“…Further evidence of the targeting of TDO by antidepressant drugs was provided by our group, using molecular docking in silico : A technique for screening potential inhibitors of target proteins[ 14 , 15 ], but is also useful to confirm known inhibitors. We demonstrated high docking scores (strong binding) of many antidepressants, including amoxapine, citalopram, fluoxetine, fluvoxamine, moclobemide, paroxetine, seproxetine, sertraline[ 16 ], tianeptine and venlafaxine, but not the non-antidepressant drugs pargyline and mefenamic acid[ 17 ] to the crystal structure of TDO, but no docking to that of the extrahepatic IDO. Thus, antidepressants target TDO and this could explain their ability to restore serotonin homeostasis, at least in part, by reversing the defective serotonin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As this cytokine is an IDO inducer, the concept that serotonin deficiency in MDD is underpinned by IDO induction secondarily to inflammation was born. Extrapolating from hepatitis C to MDD was however unwise, given that Trp metabolism is already compromised by this virus and the use of IFN-α can only potentiate the effect of the virus on Trp metabolism, in particular IDO induction[ 17 ]. Although many studies of the immune status in MDD followed, recent studies suggested that not all MDD patients are immune-activated and, when present, inflammation is mild and/or transient and its reversal does not reflect clinical outcome[ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%